(untitled) (Research, Society and Development, 2022)
Objective. The aim was to evaluate the potential impact on interprofessional collaboration and oral health-related quality of life from a prenatal care protocol. Method. We conducted an intervention study, with a post-test control group within a mixed-methods approach. The study population comprised 60 pregnant and health professionals enrolled in primary healthcare units. In the tested protocol, oral health technician was an important link with other members of multi-professional teams in the conversation wheels within which values, perceptions, behaviors and needs of pregnant women were shared about changes experienced during the pregnancy. Numerical data and narratives were used to assess self-rated oral health, oral health-related quality of life measured by OHIP-14, perception of pregnant women on interprofessional practices. Results. Patients were young and had incomplete or complete high school with no significant differences between the test and control groups. The perception of women in relation to interprofessional collaboration was greater in the intervention group than in control group. Self-rated oral health and oral health-related quality of life improved after intervention. Conclusions. The intervention encouraged the empowerment of the team to refocus the work process with greater involvement and collaborative professional interaction favored by oral health technician performance. The service organization protocol caused tensions and produced positive effects on interprofessional collaboration and on oral health-related quality of life. Clinical Relevance. The findings showed the relevance of the oral health technician’s performance integrating the activities between dental team and multidisciplinary professional team for quality of life related to oral health and interprofessional collaboration.